Factors influence medical tourists’ satisfaction and their revisit intention to Malaysia - Te, Lee Thing; Loh, Zi Yi; Lew, Yi Qi; Tan, Wendy; Woo, Pei Kei (2019)
Medical Tourism has emerged as an area of interest for tourists to travel across international borders to seek for medical services. This has intensified the competition of medical industry among countries. The main purpose of this research is to study whether the three variables: medical service quality, perceived value and health information technology will affect medical tourists' satisfaction in Malaysia. Furthermore, satisfaction of medical tourists also affecting their revisit intention. In this study, the survey was conducted and questionnaires were distributed to 410 medical tourist respondents which located at Kuala Lumpur, Ipoh, Penang, Perak and Selangor in Malaysia. SAS software version 7.1 was used to generate the data collected and we had used Reliability analysis to test the research model. The results show that all the variables (medical service quality, perceived value and health information technology) have the positive relationships with satisfaction and health information technology indicated the strongest influence. Further, patient’s satisfaction is positively related to revisit intention for medical services. This study has provided implication for government, medical institutions and future researchers to gain understanding on the factors that influence the patients’ satisfaction and revisit intention towards medical tourism in Malaysia.